2009
DOI: 10.1158/0008-5472.can-08-4877
|View full text |Cite
|
Sign up to set email alerts
|

From Chronic Feed-Induced Intestinal Inflammation to Adenocarcinoma with Metastases in Salmonid Fish

Abstract: Neoplasms in fish normally show poor abilities for metastasis, and there are no reports on intestinal cancer with metastasis to other organs.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
36
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 38 publications
1
36
0
Order By: Relevance
“…30 Diet as a cause of the intestinal lesions described here was unlikely as a potential source of carcinogenesis based upon the experiment carried out at SARL. Data from the retrospective study suggest that intestinal lesions may be observed as early as 6 months of age and the sampling at 6 mo yielded no sign of preneoplastic or neoplastic intestinal changes.…”
Section: Discussionmentioning
confidence: 83%
“…30 Diet as a cause of the intestinal lesions described here was unlikely as a potential source of carcinogenesis based upon the experiment carried out at SARL. Data from the retrospective study suggest that intestinal lesions may be observed as early as 6 months of age and the sampling at 6 mo yielded no sign of preneoplastic or neoplastic intestinal changes.…”
Section: Discussionmentioning
confidence: 83%
“…Because of the lack of reliable mesenchymal markers in koi carp tissue, application was restricted to these epithelial markers. CK AE1/AE 3 clearly identified intestinal epithelial cells, also shown before (Dale et al 2009); however, in the gonad and in the liver, staining was inconclusive. This staining pattern was confirmed by our results in the reference carp tissue, with hepatocytes staining negative and inconsistent staining in ovary epithelial cells.…”
mentioning
confidence: 64%
“…First, a broad-spectrum antibody recognising most of the 19 human cyto keratins (Cytokeratin [CK] AE1/AE3, Dako; dilution 1:50) was used. Specificity is described for a number of fish species, including striped bass Morone saxa tilis and medaka Oryzias latipes (Bunton 1993) or Atlantic salmon Salmo salar and rainbow trout Oncorhynchus mykiss (Dale et al 2009). To test the re activity in carp tissue, normal carp liver, intestine and gonads (ovary and testis) were tested and a score was formulated according to low, moderate or strong signals obtained (Table 1, Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemistry has recently found its application in phenotyping fish neoplasms, such as melanoma, schwannoma, or adenocarcinoma, through expression of markers such as S100 protein, calretinin, or cytokeratin (Sakamoto & White 2002, Marino et al 2007, Magi et al 2008, Marino et al 2008, Dale et al 2009). The use of mammalian antibodies in fish tissues has some limitations related to their specificity.…”
Section: Discussionmentioning
confidence: 99%